2015
DOI: 10.18632/oncotarget.3552
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS sensitizes premalignant, but not malignant cells, to Noxa-dependent apoptosis through the activation of the MEK/ERK pathway

Abstract: KRAS is mutated in about 20-25% of all human cancers and especially in pancreatic, lung and colorectal tumors. Oncogenic KRAS stimulates several pro-survival pathways, but it also triggers the trans-activation of pro-apoptotic genes. In our work, we show that G13D mutations of KRAS activate the MAPK pathway, and ERK2, but not ERK1, up-regulates Noxa basal levels. Accordingly, premalignant epithelial cells are sensitized to various cytotoxic compounds in a Noxa-dependent manner. In contrast to these findings, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…This would provide a ‘decision point’ for entry into apoptosis, which is triggered either by a stoichiometric excess of NOXA over MCL1, or upon activation of additional pro-apoptotic BH3 proteins by compounds such as ABT-737. In support of this, concomitant NOXA and MCL1 upregulation is observed in MYC-driven leukemias [ 49 ], and following activation of RAS in epithelial cells [ 50 ]. Furthermore, despite concomitant upregulation of NOXA and MCL1, squamous cell carcinomas retain sensitivity to ABT-737 due to an increased NOXA:MCL1 ratio [ 36 ].…”
Section: Discussionmentioning
confidence: 88%
“…This would provide a ‘decision point’ for entry into apoptosis, which is triggered either by a stoichiometric excess of NOXA over MCL1, or upon activation of additional pro-apoptotic BH3 proteins by compounds such as ABT-737. In support of this, concomitant NOXA and MCL1 upregulation is observed in MYC-driven leukemias [ 49 ], and following activation of RAS in epithelial cells [ 50 ]. Furthermore, despite concomitant upregulation of NOXA and MCL1, squamous cell carcinomas retain sensitivity to ABT-737 due to an increased NOXA:MCL1 ratio [ 36 ].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, ERK‐dependent up‐regulation of NOXA by mutant KRAS is also able to sensitise premalignant human epithelial cells to the combination of a SMAC mimetic (SM83) and camptothecin (CPT). However, this effect on NOXA and sensitisation to SM83/CPT is lost in malignant colorectal cancer cells with KRAS mutations due to aberrant activation of PI3K‐dependent survival signalling . This effect was attributed to PKB/AKT activation using the tricyclic nucleoside Triciribine, an inhibitor of DNA synthesis that has also shown potent activity against PKB/AKT, but was not confirmed using PKB/AKT‐specific RNAi.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the preceding examples, the BH3‐only protein NOXA is very clearly induced rather than repressed by ERK1/2 signalling. For example, activation of ERK1/2 by activated mutant HRAS drives NOXA mRNA and protein expression, whereas inhibition of ERK1/2 signalling in tumour cells with pathway deregulation, such as BRAF 600E in melanoma, reduces NOXA levels . In terms of mechanism it appears that ERK1/2 signalling drives NOXA transcription via CREB; a CREB‐binding site in the NOXA 5′‐UTR was required for BRAF 600E ‐driven expression of a NOXA ‐driven reporter construct while CREB phosphorylation was commensurate with NOXA expression .…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that Noxa expresses in colorectal cancers, malignant melanomas and ameloblastomas [36,37,38,39], and that it is involved in the mechanism of action of the anticancer agents bortezomib and pemetrexed [40,41,42,43,44,45,46,47]. However, the expression of Noxa in mesothelioma cells has so far not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been reported that oncogenic activation of MEK/ERK drives Noxa expression to promote autophagy, and Noxa displays indirect antiapoptosis activity in malignant melanoma [38]. Oncogenic activation of MEK/ERK drives Noxa expression in colorectal cancer, but the activated PI3K/AKT pathway counterbalances Noxa, leading to apoptotic changes [39]. It is possible that similar mechanism acts in the mesothelioma.…”
Section: Discussionmentioning
confidence: 99%